2016
DOI: 10.15366/rimcafd2016.61.007
|View full text |Cite
|
Sign up to set email alerts
|

Modificación del volumen-intensidad como medida preventiva de lesiones en fútbol sala / Modification of volume-intensity as preventive measure in futsal injuries

Abstract: RESUMENA lo largo de los años se han desarrollado distintas metodologías para controlar las cargas de entrenamiento y optimizar el rendimiento. La prevención de lesiones se ha convertido en uno de los grandes objetivos del cuerpo técnico. Algunos estudios plantean que variables como el volumen de trabajo, la intensidad y la frecuencia en su realización pueden ser la clave para lograrlo. El propósito de este trabajo es analizar en qué magnitud han influido las diferentes medidas preventivas adoptadas referidas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
4
0
3
Order By: Relevance
“…With respect to the location of futsal-related injuries, and similar to previous studies in male (Ribeiro, Oliveira & Costa, 2006; Junge & Dvorak, 2010; Álvarez Medina et al, 2016) and female futsal players (Angoorani et al, 2014; Hamid, Jaafar & Ali, 2014), lower extremity injuries were, by far, the most frequent injuries (83.3% of all the injuries recorded). The thigh (50% of all the injuries recorded) was the anatomical region of the lower extremity where injuries occurred significantly more followed by the knee (6.7% of all the injuries recorded) and ankle (6.7% of all the injuries recorded).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…With respect to the location of futsal-related injuries, and similar to previous studies in male (Ribeiro, Oliveira & Costa, 2006; Junge & Dvorak, 2010; Álvarez Medina et al, 2016) and female futsal players (Angoorani et al, 2014; Hamid, Jaafar & Ali, 2014), lower extremity injuries were, by far, the most frequent injuries (83.3% of all the injuries recorded). The thigh (50% of all the injuries recorded) was the anatomical region of the lower extremity where injuries occurred significantly more followed by the knee (6.7% of all the injuries recorded) and ankle (6.7% of all the injuries recorded).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, while in their study the Malaysian league had a duration of approximately 22 weeks (1st July until 28th November) with a break in August (because of fasting during Ramadan) and one or two matches per week, the three seasons (2015–2018) of the Spanish second division analyzed in the current study lasted 8 months (average of 34.3 ± 2.1 weeks) with two breaks periods of 2–3 weeks (at Christmas and Easter) with one match played per week (usually at the weekend days). This hypothesis may be supported by evidence from prospective epidemiological studies carried out in elite male futsal players (Ribeiro, Oliveira & Costa, 2006; Junge & Dvorak, 2010) and football players (Dvorak et al, 2011; Junge & Dvořák, 2015) during international tournaments (i.e., World cups) which have shown higher incidence rates in comparison with those conducted during national league futsal (Hamid, Jaafar & Ali, 2014; Álvarez Medina et al, 2016) and football (Noya Salces et al, 2014; Stubbe et al, 2015). This is likely due to the higher match demands during international tournaments with relatively shorter recovery times between matches.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…With regard to the reporting quality of the studies selected in this systematic review and meta-analysis, five out of the six studies achieved STROBE scores that were categorized as high (18 , 19 (Angoorani et al, 2014;Hamid et al, 2014; and 20 (Ruiz-Pérez et al, 2019) points out of the 22-maximum achievable) while only one study (Álvarez Medina et al, 2016) demonstrated a STROBE score that was categorized as low ( 13points). Regarding the assessment of the risk of bias of external validity quality, all the studies selected obtained seven out of eight stars in the NOS scale, with the exception of the study conducted by Álvarez- which was awarded only 5 stars.…”
Section: Quality and Risk Of Bias Assessment Of The Studies Selectedmentioning
confidence: 99%
“…However, before implementing any injury prevention measure it is essential to know the injury profile of futsal, in terms of incidence, severity and location of the most common injuries (Finch, 2006;van Mechelen, Hlobil, & Kemper, 1992;Van Tiggelen, Wickes, Stevens, Roosen, & Witvrouw, 2008). Currently, the available prospective epidemiological studies in futsal that report time-loss injury incidence data have shown incidence rates that range from 0.9 to 195.6 and from 6.7 to 86.6 injuries per 1000 hours of male (Álvarez Medina, Murillo Lorente, Giménez Salillas, & Manonelles Marqueta, 2016;Angoorani, Haratian, Mazaherinezhad, & Younespour, 2014;Ribeiro, Oliveira, & Costa, 2006) and female (Angoorani et al, 2014;Hamid, Jaafar, & Ali, 2014;Ruiz-Pérez et al, 2019) players exposure, respectively. This large variation in injury incidence exhibited by futsal epidemiological studies may be attributed to differences in the number of players included in these studies and the competition analyzed (e.g.…”
Section: Introductionmentioning
confidence: 99%